Victor Avila: capstone - Avila, Victor, artist (Colorado State University. Libraries, 2019)
The artist's statement: Design is imperative in identifying an idea and what it represents. Understanding the communication between a composition and a consumer is what I specialize in. My work consists of stages of a process that revolves around visualization, sketching, drafting, and refining. With my design nothing is a mistake, every element is thought out and placed strategically throughout the composition. Graphic Design is the study and execution of the process of visual communication, my design is made to spark interest, evoke emotion, create conflict, and result in an interaction between the opinion of the viewer and the message of my composition. A component of my design process, and perhaps the most import is the research that initiates any project or idea. Research is used to choose the direction of the message and emotion; execution is the style and placement. I take a lot from my drawing background and like to start every design by hand sketching. With this stage quantity over quality is the goal when exploring design possibilities, this is because a more diverse set of beginnings can lead to a unique style of composition. This step is the most significant in my design process as the sketching allows for my design to blend different forms of media to create designs that are striking and layered. Refining happens digitally, as well as any text or photo elements. Even once finished, digital projects are moved to the physical realm as printing and displaying become the next crucial aspects of my work. Paper variety and unconventional ways of presentation are the final vessel of my visual communication, for the project to be considered quality it has to be consumed in the best way possible as well. Mockups are an important part of the creative process as being able to see the design in how it communicates with consumers allows me insight in how people choose to see. The idea of the method of seeing is different for individuals, which means each project will leave each viewer with a different experience. Knowing this helps my work in its variety and changing of rules in order to create new ones that will eventually be broken as well. My process and style of design is created through discipline and free thinking, it is what makes me a graphic designer.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design